THE USAGE OF JARIMATIKA METHODS TO IMPROVE COUNTING SKILLS ABILITY FOR LOW-GRADE STUDENTS - Ihsanudin Ihsanudin; Trian Pamungkas Alamsyah (Universitas Muria Kudus, 2019)
The purpose of this research is to find the usage of Jarimatika method in improving counting skills ability for low grade students on multiplication 6 to 10. The method used in this study is a quasi-experimental method. The sample of this study is grade III elementary school. Sample selection by purposive sampling. The study was conducted at SD Banjar Agung 4 Serang Regency with a population of all class III at the elementary school. Data was collected using several techniques of documentation, observation, tests and interviews. This study uses a prerequisite test that is normality test and homogeneity test using SPSS 19 program. The results of this study, there is an improvement in students' counting skills on multiplication 6 to 10 which can be seen by increasing the average score of students in the post test and based on the calculation of the t test with a significant value of 0.343 (exceeded the value of 0.05) and students are more enthusiastic and not quickly forget the multiplication calculation.